Vegetable seed production under protected and open field conditions in India: A review - SINGH, BALRAJ; TOMAR, B S (The Indian Journal of Agricultural Sciences, 2015)
Vegetable crops faces tremendous challenges in the production of disease free, healthy and genetically pure seed for commercial cultivation. Conventional practices of seed production in open fields’ faces common problems like lack of sufficient isolation, insects, diseases and a virus free environment. Compared to conventional practices, protected cultivation can deliver higher seed yield with better quality. Insects and viruses are the most devastating problems for quality seed production in most of the vegetable crops in open fields, and if the insect vectors are checked by using protected structures this problem could be solved with less application of pesticides. An innovation applicable in a very practical manner is always likely to get popularity to the assumed potential resulting in significant profit to the stakeholders. Seed production under protected conditions is a best example of it. A decade ago, research on seed production under protected conditions was initiated in India and tremendous work has been carried out to standardize the technology, i.e. for quality seed production realizing the various biotic and abiotic stress problems encountered in open field seed production programmes. The present review provides comprehensive information on significant research work done in India in hybrid seed production of vegetables under various protected and open field environment. This concept has shown significant results not only in quality seed production but also in increasing the per unit seed yield in different vegetables. The protected cultivation models has proved to be highly economical and profitable with limited resources and man power to provide best quality seeds of numerous vegetables cultivated in India and across the globe.